Inorganic fire-resistant coating for building and preparation method thereof

The preparation of spiral fibers by reacting dihydroxyethylcyclohexylamine with sodium silicate and composite electrospinning solves the problems of volume shrinkage and internal stress during the drying of inorganic coatings, and significantly improves crack resistance and stability.

CN119019877BActive Publication Date: 2024-12-20GUANGZHOU FUTIAN CHEM IND COATINGS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411499842.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2024-12-20
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The volume shrinkage of inorganic coatings during drying is too large, resulting in increased internal stress and crack problems. The crack resistance in the prior art is limited.

Method used

Dihydroxyethylcyclohexylamine reacts with sodium silicate to form silicon-oxygen-carbon bonds, reduce volume shrinkage, and prepare spiral fibers by composite electrospinning to enhance the strength and toughness of the fibers, and form a buffer layer to reduce stress transfer.

Benefits of technology

Effectively reduce volume shrinkage and internal stress during the paint drying process, improve crack resistance, and enhance the stability and crack resistance of the paint.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119019877B_ABST
    Figure CN119019877B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of inorganic coatings, and specifically discloses an inorganic refractory coating for construction and a preparation method thereof. An inorganic refractory coating for construction comprises the following components: sodium silicate, filler, titanium dioxide, bentonite, defoamer, dispersant, thickener, dihydroxyethyl cyclohexylamine, and spiral fiber. The inorganic refractory coating for construction prepared by the present application has the advantage of anti-cracking.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of inorganic coatings, and more specifically, to an inorganic fire-resistant coating for construction and a preparation method thereof. Background Art

[0002] As people's environmental awareness continues to improve, the environmental protection requirements for architectural coatings are becoming more and more stringent. Traditional organic coatings will add a large amount of volatile organic matter during the production process. These volatile organic matter will continue to be released into the environment during the subsequent use of the coating, causing environmental pollution. The content of volatile organic matter in inorganic coatings is extremely low or even zero, making it the first choice for environmentally friendly architectural coatings.

[0003] Compared with organic coatings, inorganic coatings will experience greater volume shrinkage during the drying process. This is because organic coatings contain a large amount of high molecular polymers. During the drying process, the high molecular polymers polymerize into films with small volume changes. The film-forming substances in inorganic coatings are mainly small molecular compounds. During drying, the small molecules polymerize into films with large volume changes. If the volume shrinks too much during the drying process of the coating, it will produce large internal stress and cause cracks on the coating surface. Therefore, it is more important to solve the cracking problem of inorganic coatings during the drying process.

[0004] The Chinese patent application document with publication number CN115368075A discloses a building coating and its preparation method and application, the building coating comprises the following components: silicate ore powder, silicate ore sand, silicate cement, waste slag powder, granulated blast furnace, slag powder, hydroxymethyl cellulose, alkali-resistant glass fiber, waste slurry water, water reducer, defoamer, early strength agent. The building coating selects silicate cement, waste slag powder and granulated blast furnace slag powder as basic binders, and hydroxymethyl cellulose, alkali-resistant glass fiber, waste slurry water, water reducer, defoamer, early strength agent, etc. as mixing agents and functional adjuvants, which can prevent the coating from cracking.

[0005] In the above-mentioned documents, the anti-cracking performance of the coating is improved by adding substances such as alkali-resistant glass fiber, but due to the limitations of the performance of the alkali-resistant glass fiber itself, the ability to prevent the coating from cracking is limited. Summary of the invention

[0006] In order to further improve the anti-cracking performance of inorganic refractory coatings for construction, the present application provides an inorganic refractory coating for construction and a preparation method thereof.

[0007] In the first aspect, the present application provides an inorganic refractory coating for construction, which adopts the following technical solution:

[0008] An inorganic fire-resistant coating for construction comprises the following components in parts by weight: 90-100 parts of sodium silicate, 25-35 parts of filler, 25-35 parts of titanium dioxide, 1-2 parts of bentonite, 1-2 parts of defoamer, 2-4 parts of dispersant, 2-4 parts of thickener, 8-11 parts of dihydroxyethylcyclohexylamine, 5-10 parts of spiral fiber and 100-110 parts of deionized water.

[0009] The method for preparing the spiral fiber comprises the following steps:

[0010] (1) Evenly mixing hydrophobically modified xanthan gum, deionized water and acetic acid to obtain spinning solution A;

[0011] (2) uniformly mixing hydroxyethyl cellulose, thermoplastic polyurethane and dimethylacetamide to obtain spinning solution B;

[0012] (3) Spinning solution A and spinning solution B are respectively injected into two identical syringes for composite electrospinning, and the fibers obtained by composite electrospinning are dried and crushed to obtain spiral fibers.

[0013] By adopting the above technical scheme, dihydroxyethyl cyclohexylamine participates in the film-forming process of sodium silicate, reducing the volume shrinkage rate of the coating during the drying process, thereby reducing the internal stress of the coating; when the stress generated inside the coating acts on the spiral fibers, the spiral fibers stretch and twist, consuming this part of the stress, reducing the stress transmitted inside the coating, and improving the coating's anti-cracking performance.

[0014] Preferably, in step (1), the method for preparing hydrophobically modified xanthan gum comprises the following steps:

[0015] Under nitrogen bubbling conditions, hexadecane bromide, dimethylformamide and sodium hydroxide are mixed evenly, the reaction temperature is 60-70°C, xanthan gum is added in batches, stirred for 8-10 hours, ethanol is added, the solid product is separated by filtration, washed, and dried to obtain hydrophobically modified xanthan gum.

[0016] By adopting the above technical scheme, the hydrophilicity of the hydrophobically modified xanthan gum is reduced, the hydrophobicity is enhanced, the stability in the spiral fiber is highly enhanced, the strength and toughness of the spiral fiber are improved, and the spiral fiber has a higher stress bearing capacity; and the number of long branches on the main chain of the hydrophobically modified xanthan gum molecule is increased, thereby increasing the steric hindrance of the hydrophobically modified xanthan gum.

[0017] Preferably, the mass ratio of the sodium hydroxide, hexadecane bromide and xanthan gum is 1:(5-7.3):(60-65).

[0018] By adopting the above technical scheme, the prepared hydrophobic modified xanthan gum has a suitable ratio of hydrophobic xanthan gum and hydrophilic xanthan gum. The hydrophilic part of the hydrophobic modified xanthan gum in the coating is stretched out to form a buffer layer on the surface of the spiral fiber, which reduces the relative movement rate of the molecules in the coating, prevents the coating from drying too fast in the early stage, and makes the coating have good anti-cracking performance.

[0019] Preferably, in step (1), the mass ratio of hydrophobically modified xanthan gum, deionized water and acetic acid is 1:(2.3-3.3):(2.8-4).

[0020] By adopting the above technical scheme, a spinning solution A with good stability is obtained. When performing composite electrospinning, the spinning solution A and the spinning solution B have better compatibility. The prepared fiber has a better surface structure and internal structure, and the stability of the fiber is enhanced, so that the stress bearing capacity of the fiber is stronger.

[0021] Preferably, in step (2), the mass ratio of hydroxyethyl cellulose, thermoplastic polyurethane and dimethylacetamide is 1:(2.5-4.5):(10-14).

[0022] By adopting the above technical scheme, during the composite electrospinning process, the solvent can be fully evaporated, so that the internal and surface structures of the fibers are intact, the fiber strength and toughness are improved, and the ability to withstand stress is enhanced; and when the fibers exist in the coating, they have appropriate steric hindrance, which neither has a significant impact on the strength and toughness of the fibers, but also can reduce the movement rate of the molecules in the coating and slow down the initial drying rate of the coating.

[0023] Preferably, in step (3), the process parameters of electrospinning are: voltage 20-30 kV, receiving distance 15-20 cm, feed rate 2-5 mL / h; the nozzle of composite electrospinning is a side-by-side nozzle.

[0024] By adopting the above technical solution, the obtained fibers have good toughness and high strength while having a small specific surface area, and the fiber morphology is good. By using side-by-side nozzles for composite electrospinning, the obtained fibers have a good spiral structure and can consume more stress.

[0025] Preferably, in step (3), the average length of the fibers after crushing is 3-6 mm.

[0026] By adopting the above technical scheme, while fully demonstrating the good strength and toughness of the spiral fibers, the spiral fibers also have good dispersibility in the paint, and the spiral fibers have better ability to rotate and twist when subjected to stress, which can quickly consume the stress in the paint, reduce the adverse effects of stress on the paint during use, and increase the stability and crack resistance of the paint.

[0027] Preferably, the filler is two of shell powder, quartz powder, talcum powder and heavy calcium.

[0028] By adopting the above technical solution, the porous structure of shell powder can absorb a certain amount of water, slowing down the volatilization rate of water during the drying process of the coating. The lamellar structure of talcum powder can span the cracks and withstand a certain stress, thereby preventing the cracks from further expanding and improving the anti-cracking performance of the coating. Quartz powder and heavy calcium can play a skeleton filling role, increasing the shape stability and strength of the coating. In addition, shell powder, quartz powder, talcum powder and heavy calcium help stabilize the position and shape of the fibers, reduce the movement and deformation of the fibers in the coating, and thus maintain the stability of the coating performance.

[0029] Preferably, the defoamer is one of A-601 defoamer, HS01 defoamer and SB520 defoamer.

[0030] By adopting the above technical solution, bubbles in the coating can be quickly eliminated under high shear force, the internal stress caused by bubbles can be reduced, and the anti-cracking performance of the coating can be improved. It can also promote the interface bonding between the fiber and the coating, enhance the adhesion of the coating to the fiber, and improve the overall performance of the coating.

[0031] Preferably, the dispersant is one of Dispers 655, Dispersant 5040 and Dispersant 5027.

[0032] By adopting the above scheme, the coating has higher dispersion stability, and the shrinkage stress of each part of the coating during the drying process is more uniform, avoiding large stress concentration caused by local pigment aggregation, thereby improving the coating's anti-cracking performance. The fiber is better combined with the coating matrix, preventing aggregation and flocculation between particles, so that the fiber maintains a good dispersion state in the coating. It can also improve the compatibility of the fiber with other components of the coating through interaction with the fiber surface, thereby improving the strength and durability of the coating.

[0033] Preferably, the thickener is one of sodium carboxymethyl cellulose, carboxyethyl cellulose and hydroxyethyl cellulose.

[0034] By adopting the above technical solution, the coating can be prevented from sagging and flowing during use, ensuring uniform coating thickness. Uniform coating thickness can reduce the internal stress caused by thickness differences and reduce the possibility of coating cracking. It can improve the suspension of fibers in the coating, making the fibers evenly dispersed in the coating system, and preventing fiber sedimentation and stratification.

[0035] In a second aspect, the present application provides a method for preparing an inorganic refractory coating for construction, comprising the following steps: uniformly mixing sodium silicate, filler, titanium dioxide, bentonite, defoamer, dispersant, thickener, dihydroxyethylcyclohexylamine, spiral fiber, and deionized water to obtain an inorganic refractory coating for construction.

[0036] In summary, this application has the following beneficial effects:

[0037] 1. The two hydroxyl groups in the dihydroxyethylcyclohexylamine used in the present application form hydrogen bonds with the silanol groups in the sodium silicate. During the drying process of the coating, a molecule of water is lost between the dihydroxyethylcyclohexylamine and the silicon dioxide molecule to form a silicon-oxygen-carbon bond. The dihydroxyethylcyclohexylamine participates in the formation of a three-dimensional silicon-oxygen network structure, which reduces the volume shrinkage rate of the silicon-oxygen network structure during the dehydration and drying process, and reduces the risk of coating cracking.

[0038] 2. The spiral fiber can consume the internal stress of the coating by stretching and twisting itself, and prevent the coating from cracking. These stresses include the internal stress caused by volume shrinkage during the coating drying process and the stress caused to the coating by the unstable environment during the subsequent use process. The spiral fiber prepared by the present application contains water-soluble hydroxyethyl cellulose and hydrophobically modified xanthan gum that can be slightly soluble in water. In the coating, the fiber surface will stretch out hydroxyethyl cellulose and hydrophobically modified xanthan gum long chains, forming a buffer layer on the spiral fiber surface, hindering the free movement of water molecules, reducing the migration rate of water molecules to the surface, preventing the coating from drying too fast in the early stage, and being conducive to the neat arrangement of dihydroxyethyl cyclohexylamine and sodium silicate molecules, making the silicon oxygen three-dimensional network structure formed by dihydroxyethyl cyclohexylamine more regular, improving the stability of the coating film, and increasing the anti-cracking performance of the coating during the drying process.

[0039] 3. After the spiral fibers prepared in the present application are added to the coating, the hydroxyethyl cellulose and hydrophobically modified xanthan gum long chains dissolved from the surface of the spiral fibers will interact well with other components in the coating, promoting good compatibility between the spiral fibers and other components in the coating, and the spiral fibers can exist stably in the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 : Electron microscope photograph of the spiral fiber prepared in Example 1 of the present application.

[0041] Figure 2 : Infrared spectra of the sodium silicate and dihydroxyethylcyclohexylamine aqueous solution after curing in this application.

[0042] Figure 3 : Infrared spectrum of the hydrophobically modified xanthan gum prepared in Example 1 of the present application. DETAILED DESCRIPTION

[0043] The present application is further described in detail below with reference to the embodiments.

[0044] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0045] Example 1

[0046] The inorganic refractory coating for construction in this embodiment is composed of the following components: 90g of sodium silicate, 15g of shell powder, 10g of heavy calcium, 35g of titanium dioxide, 1g of bentonite, 1g of A-601 defoamer, 2g of Dispers 655, 2g of sodium carboxymethyl cellulose, 8g of dihydroxyethyl cyclohexylamine, 5g of spiral fiber, and 100g of deionized water.

[0047] The preparation method of the spiral fiber of this embodiment is as follows:

[0048] (1) 10 g of hydrophobically modified xanthan gum, 23 g of deionized water and 28 g of acetic acid were uniformly mixed to obtain spinning solution A;

[0049] (2) 1 g of hydroxyethyl cellulose, 15 g of thermoplastic polyurethane and 70 g of dimethylacetamide were uniformly mixed to obtain a spinning solution B;

[0050] (3) Spinning solution A and spinning solution B were respectively injected into two identical syringes for composite electrospinning. The voltage of composite electrospinning was 20 kV, the receiving distance was 15 cm, the feed rate of the two syringes was 2 mL / h, and the nozzle of composite electrospinning was a side-by-side nozzle. The diameter of the obtained fiber was 10 μm. The obtained fiber was dried and then crushed into a state with an average length of 3 mm to obtain spiral fiber.

[0051] The preparation method of the hydrophobically modified xanthan gum of the present embodiment is as follows:

[0052] Put 0.73g of hexadecane bromide, 150g of dimethylformamide and 0.1g of sodium hydroxide into a three-necked flask, stir and mix evenly under nitrogen bubbling, raise the reaction temperature to 60°C, add 3g of xanthan gum, stir for 5h, then add 2g of xanthan gum, stir for 3h, then add 1.5g of xanthan gum, stir for 2h, add 120g of ethanol, filter and separate the solid product, wash and dry to obtain hydrophobically modified xanthan gum.

[0053] The preparation method of the inorganic refractory coating for construction of the present embodiment is as follows:

[0054] Put 100g of deionized water and 90g of sodium silicate into a beaker and mix evenly, then add 8g of dihydroxyethylcyclohexylamine and mix evenly, then add 1g of A-601 defoamer, 2g of Dispers 655, 2g of sodium carboxymethyl cellulose, 1g of bentonite and mix evenly, then add 5g of spiral fiber, 35g of titanium dioxide and 15g of shell powder, 10g of heavy calcium and mix evenly to obtain an inorganic refractory coating for construction.

[0055] Example 2

[0056] The inorganic refractory coating for construction in this embodiment is composed of the following components: 100g sodium silicate, 15g talcum powder, 20g shell powder, 25g titanium dioxide, 2g bentonite, 2g SB520 defoamer, 4g dispersant 5027, 4g hydroxyethyl cellulose, 11g dihydroxyethyl cyclohexylamine, 10g spiral fiber, and 110g deionized water.

[0057] The preparation method of the spiral fiber of this embodiment is as follows:

[0058] (1) 15 g of hydrophobically modified xanthan gum, 49.5 g of deionized water and 60 g of acetic acid were uniformly mixed to obtain spinning solution A;

[0059] (2) 1 g of hydroxyethyl cellulose, 22.5 g of thermoplastic polyurethane and 82 g of dimethylacetamide were uniformly mixed to obtain a spinning solution B;

[0060] (3) Spinning solution A and spinning solution B were respectively injected into two identical syringes for composite electrospinning. The voltage of composite electrospinning was 30 kV, the receiving distance was 20 cm, the feed rate of the two syringes was 5 mL / h, and the nozzle of composite electrospinning was a side-by-side nozzle. The diameter of the obtained fiber was 9 μm. The obtained fiber was dried and then crushed into a state with an average length of 6 mm to obtain spiral fiber.

[0061] The preparation method of the hydrophobically modified xanthan gum of the present embodiment is as follows:

[0062] Put 1g of hexadecane bromide, 250g of dimethylformamide and 0.2g of sodium hydroxide into a three-necked flask, stir and mix evenly under nitrogen bubbling, increase the reaction temperature to 70°C, add 5g of xanthan gum, stir for 4h, then add 5g of xanthan gum, stir for 3h, then add 2g of xanthan gum, stir for 1h, add 200g of ethanol, filter and separate the solid product, wash and dry to obtain hydrophobically modified xanthan gum.

[0063] The preparation method of the inorganic refractory coating for construction of the present embodiment is as follows:

[0064] Put 110g of deionized water and 100g of sodium silicate into a beaker and mix evenly, then add 11g of dihydroxyethylcyclohexylamine and mix evenly, then add 2g of SB520 defoamer, 4g of dispersant 5027, 4g of hydroxyethyl cellulose, and 2g of bentonite and mix evenly, then add 10g of spiral fiber, 25g of titanium dioxide, 15g of talcum powder, and 20g of shell powder and mix evenly to obtain an inorganic refractory coating for construction.

[0065] Example 3

[0066] The inorganic refractory coating for construction in this embodiment is composed of the following components: 93g sodium silicate, 22g talcum powder, 9g quartz powder, 26g titanium dioxide, 1.2g bentonite, 1.5g HS01 defoamer, 3g dispersant 5040, 2.5g carboxyethyl cellulose, 9g dihydroxyethyl cyclohexylamine, 6g spiral fiber, and 108g deionized water.

[0067] The preparation method of the hydrophobically modified xanthan gum of the present embodiment is as follows:

[0068] Put 0.6g of hexadecane bromide, 140g of dimethylformamide and 0.1g of sodium hydroxide into a three-necked flask, stir and mix evenly under nitrogen bubbling, raise the reaction temperature to 67°C, add 3.4g of xanthan gum, stir for 4h, then add 2g of xanthan gum, stir for 4h, then add 1g of xanthan gum, stir for 1h, add 120g of ethanol, filter and separate the solid product, wash and dry to obtain hydrophobically modified xanthan gum.

[0069] The preparation method of the spiral fiber of this embodiment is as follows:

[0070] (1) 10 g of hydrophobically modified xanthan gum, 25 g of deionized water and 32 g of acetic acid were uniformly mixed to obtain spinning solution A;

[0071] (2) 1 g of hydroxyethyl cellulose, 18 g of thermoplastic polyurethane and 76 g of dimethylacetamide were uniformly mixed to obtain spinning solution B;

[0072] (3) Spinning solution A and spinning solution B were respectively injected into two identical syringes for composite electrospinning. The voltage of composite electrospinning was 23 kV, the receiving distance was 16 cm, the feed rate of the two syringes was 3 mL / h, and the nozzle of composite electrospinning was a side-by-side nozzle. The diameter of the obtained fiber was 10 μm. The obtained fiber was dried and then crushed into a state with an average length of 4 mm to obtain spiral fiber.

[0073] The preparation method of the inorganic refractory coating for construction of the present embodiment is as follows:

[0074] Put 108g of deionized water and 93g of sodium silicate into a beaker and mix evenly, then add 9g of dihydroxyethylcyclohexylamine and mix evenly, then add 1.5g of HS01 defoamer, 3g of dispersant 5040, 2.5g of carboxyethyl cellulose, 1.2g of bentonite and mix evenly, then add 6g of spiral fiber, 26g of titanium dioxide, 22g of talc, and 9g of quartz powder and mix evenly to obtain an inorganic refractory coating for construction.

[0075] Comparative Example 1

[0076] The difference between this comparative example and Example 1 is that an equal amount of glass fibers are used instead of spiral fibers during the preparation of the inorganic refractory coating for construction.

[0077] Comparative Example 2

[0078] The difference between this comparative example and Example 1 is that an equal amount of xanthan gum is used instead of the hydrophobically modified xanthan gum during the preparation of the inorganic refractory coating for construction.

[0079] Among them, the effective ingredient content of the xanthan gum used in Examples 1, 2, 3 and Comparative Examples 1 and 2 is 99%.

[0080] Performance testing

[0081] The performance testing method of inorganic refractory coating for construction is as follows:

[0082] 1. Initial drying crack resistance

[0083] The test method for the initial drying crack resistance of inorganic refractory coatings for construction refers to the national standard GB / T9779-2015. The test board uses asbestos-free cement board, and the inorganic refractory coating for construction is applied to the surface of the asbestos-free cement board. After the coating is dry to the touch, the test board is placed on the test frame in the wind tunnel, the test board is parallel to the airflow direction, the wind tunnel fan is turned on, and the test board is taken out after 6 hours. The coating is photographed and the coating crack area rate is calculated using Image J software.

[0084] 2. Resistance to temperature change

[0085] The test method for the thermal deformation resistance of inorganic fire-resistant coatings for construction refers to the construction industry standard JG / T25-2017. The test board is an asbestos-free cement board with a length of 150 mm, a width of 200 mm, and a thickness of 5 mm. The back and four sides of the asbestos-free cement board are sealed with paraffin wax, and the number of cycles is 10. After taking pictures of the coating, the crack area rate of the coating is calculated using Image J software.

[0086] 3. Infrared spectrum test of sodium silicate and dihydroxyethylcyclohexylamine aqueous solution after curing

[0087] 100 g of deionized water and 90 g of sodium silicate were put into a beaker and mixed evenly, and then 8 g of dihydroxyethylcyclohexylamine was added and mixed evenly. After curing at room temperature, a sample was obtained, and an infrared spectrum test was performed on the sample.

[0088] The performance test data of Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 are shown in Table 1 below:

[0089]

[0090] It can be seen from the analysis of Examples 1-3, Comparative Examples 1 and 2 in combination with Table 1 that the inorganic architectural coating to which dihydroxyethylcyclohexylamine and spiral fibers are added has good anti-cracking performance.

[0091] analyze Figure 2 It can be seen that 900-1100cm -1 Si-O stretching vibration peak, 1100-1300cm -1 It is the CO stretching vibration peak.

[0092] analyze Figure 3 It can be seen that the OH stretching vibration peak of the alcohol hydroxyl group in the modified xanthan gum is at 3272.35 cm -1 The CH stretching vibration peak of methylene is at 2926.67 cm -1 The CO stretching vibration peak of the ether bond is at 1024.03 cm -1 The CH bending vibration of the para-substituted adjacent bromohexadecane is at 865.81 cm -1 Place.

[0093] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An inorganic refractory coating for construction, It is characterized in that The invention comprises the following components in parts by weight: 90-100 parts of sodium silicate, 25-35 parts of filler, 25-35 parts of titanium dioxide, 1-2 parts of bentonite, 1-2 parts of defoamer, 2-4 parts of dispersant, 2-4 parts of thickener, 8-11 parts of dihydroxyethylcyclohexylamine, 5-10 parts of spiral fiber and 100-110 parts of deionized water; The method for preparing the spiral fiber comprises the following steps: (1) Evenly mixing hydrophobically modified xanthan gum, deionized water and acetic acid to obtain spinning solution A; (2) uniformly mixing hydroxyethyl cellulose, thermoplastic polyurethane and dimethylacetamide to obtain spinning solution B; (3) Spinning solution A and spinning solution B are respectively injected into two syringes for composite electrospinning, and the fibers obtained by composite electrospinning are dried and crushed to obtain spiral fibers.

2. An inorganic refractory coating for construction according to claim 1, It is characterized in that In the step (1), the preparation method of the hydrophobically modified xanthan gum comprises the following steps: under nitrogen bubbling conditions, mixing hexadecane bromide, dimethylformamide and sodium hydroxide uniformly, raising the reaction temperature to 60-70° C., adding xanthan gum in batches, stirring for 8-10 hours, adding ethanol, filtering and separating the solid product, washing, and drying to obtain the hydrophobically modified xanthan gum.

3. An inorganic refractory coating for construction according to claim 1, It is characterized in that In the step (1), the mass ratio of hydrophobically modified xanthan gum, deionized water and acetic acid is 1:(2.3-3.3):(2.8-4); in the step (2), the mass ratio of hydroxyethyl cellulose, thermoplastic polyurethane and dimethylacetamide is 1:(15-22.5):(70-76).

4. An inorganic refractory coating for construction according to claim 1, It is characterized in that In the step (3), the process parameters of the composite electrospinning are: voltage 20-30 kV, receiving distance 15-20 cm, feed rate 2-5 mL / h; the electrospinning nozzle is a side-by-side nozzle.

5. An inorganic refractory coating for construction according to claim 1, It is characterized in that In the step (3), the average length of the fibers after crushing is 3-6 mm.

6. An inorganic refractory coating for construction according to claim 1, It is characterized in that The filler is two of shell powder, quartz powder, talcum powder and heavy calcium.

7. The inorganic refractory coating for construction according to claim 1, It is characterized in that The defoamer is one of A-601 defoamer, HS01 defoamer and SB520 defoamer.

8. An inorganic refractory coating for construction according to claim 1, It is characterized in that The dispersant is one of Dispers 655, Dispers 5040 and Dispers 5027.

9. An inorganic refractory coating for construction according to claim 1, It is characterized in that The thickener is one of sodium carboxymethyl cellulose, carboxyethyl cellulose and hydroxyethyl cellulose.

10. A method for preparing the inorganic refractory coating for construction as claimed in claim 1, It is characterized in that The preparation method comprises the following steps: uniformly mixing sodium silicate, filler, titanium dioxide, bentonite, defoamer, dispersant, thickener, dihydroxyethyl cyclohexylamine, spiral fiber and deionized water to obtain inorganic fire-resistant coating for construction.